Nickel-cerium bimetallic catalyst on zeolite NaA derived from kaolin for carbon dioxide methanation - Raja Nurain Nabilah, Raja Alias (2025)
CO2 is a colorless, non-flammable gas at normal temperatures and pressures. Its excessive buildup in the atmosphere absorbs solar radiation, resulting in a greenhouse effect that causes global warming and rising temperatures. Stabilizing CO2 levels is crucial for reducing climate change. Catalytic conversion is a potential strategy for converting CO2 into usable industrial products like methane. This work developed a Ni/Ce/Ru catalyst based on NaA zeolite, manufactured from natural kaolin, for CO2 methanation. The hydrothermally produced NaA zeolite had a large surface area and was thermally stable, making it an efficient support material. The catalyst, synthesized via the wet impregnation method using kaolin-derived zeolite NaA, exhibited excellent CO2 methanation performance under mild conditions (200–350ºC), achieving a maximum CO2 conversion of 82.6% at 350ºC and CH4 selectivity exceeding 90%. The optimal composition, 90Ni/10Ce/1Ru, demonstrated the synergistic role of Ce as a co-dopant and Ru as a promoter, as validated by gas chromatography. Structural characterization via Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), and Scanning Electron Microscopy (SEM) confirmed the catalyst’s enhanced properties, including active NiO (37.40º, 43.37º, 62.90º, 75.60º, 79.43º) and CeO2 (28.62º, 33.15º, 47.56º) phases, improved metal-support interactions, and thermal stability. The Ru addition caused a reduction in BET surface area (7.3656 m2/g to 5.5960 m2/g), pore volume (0.024540 cm3/g to 0.024345 cm3/g), and average pore diameter (10.275 Å to 9.730 Å), indicating structural modifications. SEM analysis further revealed a well-dispersed nanoscale morphology that prevents sintering and enhances catalytic activity. This study demonstrates the feasibility of using locally plentiful kaolin as a sustainable and cost-effective material for catalytic applications. By successfully decreasing greenhouse gas emissions and promoting renewable energy programs, the created catalyst helps to long-term solutions to global climate concerns.